Latent profile approach to duration of stalking - Björklund, K.; Häkkänen-Nyholm, H.; Sheridan, Lorraine; Roberts, K.; Tolvanen, A. (Blackwell Publishing, 2010)
Stalking behavior and victim-stalker relationship are often the principal known factors in a stalking case. Thus, they are of great importance when trying to identify factors contributing to stalking duration. The present study aims to identify distinct subgroups of stalking victims based on measures of behavioral stalking dimensions. These victim subgroups, stalking dimensions, and victim-stalker relationship are examined in relation to stalking duration. Using a sample of 137 university students, latent profile analysis (LPA) revealed five distinct victim subgroups based on stalker behavior dimensions: surveillance, low-profile, social lurker, wide scope, and baseline stalkers. The subgroups were significantly related to stalking duration and explained a considerable amount of the variance along with the stalking dimensions and victim-stalker relationship. Connections to stalking literature and utility of person-orientated methods in stalking research are discussed. © 2010 American Academy of Forensic Sciences.